Deterioration of Kaihua handmade paper: Evolution of molecular, supermolecular and macroscopic structures. (January 2022) - Yao, Jingjing; Zhang, Ruohong; Luo, Chan; Yan, Yueer; Bi, Ning; Tang, Yi
Highlights: Evolution of molecular structure of handmade papers in aging process is traced by two-dimensional correlation spectroscopy. Quantitative changes of molecular and supramolecular structures of Kaihua handmade papers in aging process are presented. The degradation mechanism of Kaihua handmade paper in dry-heat and wet-heat aging process is revealed. Correlations between the microstructural evolution and macroscopic deterioration are explained. Abstract: Valued for its toughness and durability, Kaihua paper has been famous in China since the Qing Dynasty. It attracts great attention on the extension of paper life. Understanding of the complex degradation behavior of handmade paper under various aging conditions is an essential precondition for preparing long-life handmade paper. However, it is still difficult to explain the reactions sequence of cellulose microstructure and its relationship with the macroscopic deterioration of handmade paper. Herein, different types of Kaihua handmade papers, produced by various raw materials and crafts, were artificially aged. The evolution of their multi-scale structures in dry-heat (DH) and wet-heat (WH) conditions was explored systematically. Two-dimensional correlation spectroscopy (2D-COS) distinguished possible carbonyl vibrations involving hydrolysis and oxidation of cellulose and gave sequential changes of various carbonyl groups, illustrating different evolutionary behaviors of molecular structure of papers in DH and WH aging process. The energy and distance of hydrogen bond, crystal size and microfiber accessibility were quantitatively calculated during the degradation of cellulose. In addition, correlations between microstructural evolution and macroscopic deterioration of handmade papers involving reduced mechanical properties and yellowing were revealed. The current results will help to establish a platform for the multi-scale detection of handmade paper and improve the understanding of the degradation mechanism of handmade paper under different reaction paths. It also provides useful foundation on the preparation of long-life paper and the conservation of paper-based culture relics.